Literarnozgodovinske raziskave slovenske izseljenske književnosti - Žitnik Serafin, Janja (Dve domovini, 1993)
The paper presents a survey condensed insofar as is possible on literary-historical studies published on Slovene emigration literature. The article mainly covers those studies which were published in Slovenia, and partly those which were published abroad.
Keywords: emigrantska književnost; history of literature; literarna zgodovina; Slovene literature; slovenska književnost; slovenski izseljenci; zgodovinski pregledi